Blockade of PD-1 effectively inhibits in vivo malignant transformation of oral mucosa. (1st February 2018) - Chen, Yichen; Li, Qiusheng; Li, Xinye; Ma, Da; Fang, Juan; Luo, Liqun; Liu, Xiangqi; Wang, Xi; Lui, Vivian Wai Yan; Xia, Juan; Cheng, Bin; Wang, Zhi
ABSTRACT: Curbing PD-1 immunosuppressive signaling represents an effective immune awakening or immune-reactivation approach for tumor eradication for many cancers. Yet, the potential involvement of this critical PD-1 immunosuppressive signaling in de novo malignant transformation of epithelial cells to pre-cancerous or cancerous lesions is largely unknown. In this study, we demonstrate that PD-1 signaling is critically involved in de novo malignant transformation of oral mucosa upon carcinogen exposure in vivo . Our findings revealed that 4NQO-treated mice had almost double the numbers of PD-1-positive CD4 + cells and PD-1-positive CD8 + cells in peripheral blood lymphocytes as well as elevated PD-1 expression in tumor infiltrating lymphocytes (when compared to that of control-treated mice), strongly supportive of a general immune-suppression induced by carcinogen challenges in vivo . Importantly, inhibition of PD-1 signaling during the carcinogenesis process (immediately after 4NQO challenge) significantly reduced and delayed de novo formation of both pre-cancerous and cancerous lesions in vivo, in conjunction with effective PD-1 down-modulation in the tumor infiltrating leukocyte and peripheral lymph organs. Lastly, reduction of carcinogen-induced lesions upon PD-1 mAb treatment in vivo was accompanied by reduction of potent immunosuppressive myeloid-derived suppressor cells (MDSCs), and increase in "activated" T cell accumulations in the lesion-microenvironment (127% increase) and peripheral lymph nodes (25% increase). These data support PD-1 blockade as a new approach to enhance the efficacy of T-cell immunotherapy and reduce canceration rate in premalignant lesions.